Production of linear α-olefin 1-octene via dehydration of 1-octanol over Al2O3 catalyst. (15th November 2019) - Kim, Young-eun; Im, Hyo Been; Jung, Un Ho; Park, Ji Chan; Youn, Min Hye; Jeong, Heon-Do; Lee, Dong-Wook; Rhim, Geun Bae; Chun, Dong Hyun; Lee, Ki Bong; Koo, Kee Young
Graphical abstract: Highlights: Linear α-olefin 1-octene produced via dehydration of 1-octanol over Al2 O3 catalyst. Changes in crystal phase affected the strong LAS and catalytic activity of Al2 O3 . Increased strong LAS improved 1-octanol conversion and 1-octene yield. Octene isomers decreased while DOE increased at higher LHSV. Abstract: The linear α-olefin 1-octene was produced via the dehydration of 1-octanol over Al2 O3 catalysts. The effect of calcination temperature on the characteristics of an Al2 O3 catalyst and its activity in the dehydration of 1-octanol to 1-octene was investigated. Al2 O3 catalysts calcined at various temperatures (250, 500, 750, 1000 °C) were evaluated at 300–400 °C with a liquid hourly space velocity (LHSV) of 7–56 h −1 . XRD, BET, 27 Al-NMR, Py-FTIR, and NH3 -TPD analyses indicated that the calcination temperature affected the crystal phase, surface area, occupancy of the coordinated Al 3+ ion, and acidic properties of Al2 O3 catalysts. Upon calcination at temperatures >750 °C, the surface area of Al2 O3 catalysts reduced due to γ-Al2 O3 to θ-Al2 O3 phase transition. The changes in the crystal phase decreased the surface area, which correlated to the acidity of the Al2 O3 catalyst. The distribution of unsaturated Al 3+ ions acting as LAS on the catalyst surface increased with increasing calcination temperature, but decreased above 750 °C calcination temperature due to the diminishing surface area. The Al2 O3 catalyst calcined at 500 °C showed the highest 1-octanol conversion in the dehydration of 1-octanol. High 1-octene selectivity was maintained while the isomer ratio decreased at a high LHSV of 56 h −1 .